Experimental study on CFRP strengthened cold formed channel columns - Kalavagunta S.; Naganathan S.; Bin Mustapha K.N. (Maxwell Science Publications, 2023)
Cold-formed steel members usually display local-global buckling interaction which strongly effects the structural strength of columns. Through strengthening web of the members this buckling can be controlled to some extent. In this investigation, Carbon Fibre Reinforced Polymers (CFRP) is used for strengthening cold formed steel channel member. This paper presents compression tests of cold-formed plain and CFRP strengthened steel channel section columns. This paper also proposes a design method based on Direct Strength Method provisions specified in American Iron and Steel Institute (AISI), for determining the axial compression strength. Results obtained from the proposed design method are compared with experimental test data and are found to be in good agreement. Maxwell Scientific Organization, 2013.